2007
DOI: 10.1590/s0102-79722007000200017
|View full text |Cite
|
Sign up to set email alerts
|

Uso de álcool, tabaco e drogas por estudantes da área de saúde de uma Universidade de Curitiba

Abstract: ResumoEste estudo teve por objetivo investigar o uso de álcool, tabaco e drogas por alunos da área de saúde de uma universidade particular da cidade de Curitiba. A amostra foi composta por 538 estudantes, de 18 a 54 anos, dos Cursos de Educação Física, Fisioterapia, Nutrição e Psicologia. Empregou-se para a coleta de dados o "Questionário para o levantamento do uso de álcool, drogas e condições de saúde". Os resultados apontam para um elevado consumo de álcool e tabaco, principalmente nos Cursos de Educação Fí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
46

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 18 publications
(24 reference statements)
4
30
0
46
Order By: Relevance
“…it is observed that the amount of AAS has been increasing, despite the awareness of many collateral effects, already described in the literature [7][8][9][10][11] . However, it is evidenced that there are few studies about the use of AAS among physical education students and professors [13][14][15] . Thus, considering that physical education students and teachers are individuals who make opinions, and that the level of information about the probable benefits and undesirable collateral effects may influence on the decision about using these substances and encourage the students use these drugs, the aim of this study was to verify the prevalence of the use and information about AAS by physical education students and professors who act in gyms in Belém, pA.…”
Section: Introductionmentioning
confidence: 99%
“…it is observed that the amount of AAS has been increasing, despite the awareness of many collateral effects, already described in the literature [7][8][9][10][11] . However, it is evidenced that there are few studies about the use of AAS among physical education students and professors [13][14][15] . Thus, considering that physical education students and teachers are individuals who make opinions, and that the level of information about the probable benefits and undesirable collateral effects may influence on the decision about using these substances and encourage the students use these drugs, the aim of this study was to verify the prevalence of the use and information about AAS by physical education students and professors who act in gyms in Belém, pA.…”
Section: Introductionmentioning
confidence: 99%
“…In research projects conducted by Chiapetti & Serbena 6 and Paduani et al 15 , participants reported stress as the state of mind more frequently experienced than in the study that classified it in second place. However, along with other factors that were highlighted in this study, friends and college roommates used graduation and other college parties and local use naturally mood is joy, confirmed the university environment is an exciting place for drug use.…”
Section: Discussionmentioning
confidence: 81%
“…According to the Brazilian Observatory of Drug Information 6 , 86.2% of college students reported having used alcohol at least once in their lives, the highest consumption being registered in public universities where 46.7% of students reported having used tobacco at least once in their lives and 58% reported the use of two or more drugs. The data from this same study reveal a more pronounced consumption of licit and illicit drugs by the university population than by the general population as also with respect to the risk of this behavior to their lives.…”
Section: Introductionmentioning
confidence: 99%
“…A entrada na Universidade, por ser um momento de afirmação da autonomia, muitas vezes leva aos jovens à busca destas substâncias 16 . Consumo alcoólico mais exacerbado foi encontrado em estudantes de São Paulo 19 e também num trabalho em Curitiba 20 . Entretanto, em Porto Alegre 21 , este hábito ocorria em menores proporções.…”
Section: Materiais E Métodosunclassified